Whole-Exome Sequencing Identifies Novel SCN1A and CACNB4 Genes Mutations in the Cohort of Saudi Patients With Epilepsy - Muhammad Imran Naseer; Muhammad Imran Naseer; Angham Abdulrhman Abdulkareem; Angham Abdulrhman Abdulkareem; Mahmood Rasool; Mahmood Rasool; Hussein Algahtani; Osama Yousef Muthaffar; Peter Natesan Pushparaj; Peter Natesan Pushparaj (Frontiers Media S.A., 2022)
Epilepsy is a neurological disorder described as recurrent seizures mild to severe convulsions along with conscious loss. There are many different genetic anomalies or non-genetic conditions that affect the brain and cause epilepsy. The exact cause of epilepsy is unknown so far. In this study, whole-exome sequencing showed a family having novel missense variant c.1603C>T, p. Arg535Cys in exon 10 of Sodium Voltage-Gated Channel Alpha Subunit 1 (SCN1A) gene. Moreover, targeted Sanger sequencing analysis showed c.1212A>G p.Val404Ile in SCN1A gene in 10 unrelated patients and a mutation in Calcium Voltage-Gated Channel Auxiliary Subunit Beta 4 gene where one base pair insertion of "G" c.78_79insG, p.Asp27Glyfs*26 in the exon 3 in three different patients were observed from the cohort of 25 epileptic sporadic cases. The insertion changes the amino acid sequence leading to a frameshift mutation. Here, we have described, for the first time, three novel mutations that may be associated with epilepsy in the Saudi population. The study not only help us to identify the exact cause of genetic variations causing epilepsy whereas but it would also eventually enable us to establish a database to provide a foundation for understanding the critical genomic regions to control epilepsy in Saudi patients.